Interação de microorganismos na solubilização de fósforo e potássio de rochas para produção de biofertilizantes - Silva, Valéria Nogueira da (2013)
he present model of agriculture is based on intensive use of industrial inputs, due to its rapid response, but it brings harmful consequences to the environment, and it is necessary the use of modern inputs. And an alternative is the use of rock biofertilizers in agriculture, a product easy to use, with higher residual effect and does not harm the environment. The objective of study was to evaluate the inoculation and co-inoculation of different microorganisms in the solubilization of rock phosphate and potash ground microbial evaluating the best performance in the production of biofertilizers comparing with rocks pure in soil chemical properties and, verify effect of inoculation of the bacterium Paenibacillus polymyxa in the absorption of minerals dissolved in the development of cowpea (Vigna unguiculata [L.] Walp.). The first bioassay was conducted in Laboratory (UFRN) for 72 days in Petri dishes, where the rock powder was increased by 10% and sulfur co-inoculated and inoculated with bacterial suspension of Paenibacillus polymyxa grown in medium tryptone soy broth, Ralstonia solanacearum in medium Kelman, Cromobacterium violaceum in medium Luria-Bertani and Acidithiobacillus thiooxidans in medium Tuovinen and Kelly,and fungi Trichoderma humatum and Penicillium fellutanum in malt extract. Every 12 days, samples were removed in order to build up the release curve of minerals. The second bioassay was conducted in a greenhouse of the Agricultural Research Corporation of Rio Grande do Norte in experimental delineation in randomized block designs, was used 10 kg of an Yellow Argissolo Dystrophic per pot with the addition of treatments super phosphate simple (SS), potassium chloride (KCl), pure rock, biofertilizers in doses 40, 70, 100 and 200% of the recommendation for SS and KCl, and a control, or not inoculated with bacteria P. polymyxa. Were used seeds of cowpea BRS Potiguar and co-inoculated with the bacterial suspension of Bradyrhizobium japonicum and P. polymyxa. The first crop was harvested 45 days after planting, were evaluated in the dry matter (ADM), macronutrients (N, P, K, Ca, Mg) and micronutrients (Zn, Fe, Mn) in ADM. And the second at 75 days assessing levels of macro end micronutrients in plants and soil, and the maximum adsorption capacity of P in soil. The results showed synergism in co-inoculations with P. polymyxa+R. solanacearum and, P. polymyxa+C. violaceum solubilizations providing higher P and K, respectively, and better solubilization time at 36 days. The pH was lower in biofertilizers higher doses, but there was better with their addition to P at the highest dose. Significant reduction of maximum adsorption capacity of phosphorus with increasing dose of biofertilizer. For K and Ca was better with SS+KCl, and Mg to pure rock. There was an effect of fertilization on the absorption, with better results for P, K and ADM with SS+KCL, and N, Ca and Mg for biofertilizers. Generally, the P. polymyxa not influence the absorption of the elements in the plant. In treatments with the uninoculated P. polymyxa chemical fertilizer had an average significantly higher for weight and number of grains. And in the presence of the bacteria, biofertilizers and chemical fertilizers had positive values in relation to rock and control. The data show that the rocks and biofertilizers could meet the need of nutrients the plants revealed as potential for sustainable agriculture